Establishment of Calopogonium mucunoides and Centrosema pubescens - Nazatul Biha, Abdul Rahman (Universiti Malaysia Sarawak (UNIMAS), 2014)
Fabaceae family. They are shade tolerant plant and can quickly establish a dense cover and secrete chemical substances which inhibit the growth of other weeds. In recent years, both legume species had been used as cover plant for oil palm and rubber plantation. The goal of this work was to analyze the life cycle of C. mucunoides and C. pubescens such as their germination, leaf appearance, axillary leaf appearance and seedling development. The germination test was done by incubation experiment. Whereas the vegetative development test were conducted in the field experiment by Complete Randomized Design (CRD) and quantified based on soil and air temperature. The cardinal temperature for germination and the thermal time (Tt) requirements for each vegetative development for each legumes species were quantified at the end of research. The data obtained were analysed by using least square regression. The Tt requirements for the germination in sub-optimal range were 90.9°C d for C. mucunoides and 71.4°C d for C. pubescens. The Tt requirements in supra-optimal range were 49.3°C d for C. mucunoides and 21.3°C d for C. pubescens. The It requirements for 50% of emergence were 138 (±13.0)°C d for C. mucunoides and 139 (±6.9)°C d for C. pubescens. Besides, the Tt requirements for 50% of first leaf appearance were 285 (±6.87)°C d for C. mucunoides and 279 (*7.14)°C d for C. pubescens. In addition, the It requirements for phyllochron were 160 (±7.2)°C d /leaf for C. mucunoides and 125 (±3.5)°C d /leaf for C. pubescens. The Tt requirements for axillary leaf appearance were 742 (±16.2)°C d for C. mucunoides and 747 (±6.9)°C d for C. pubescens.